Evaluation of live surgery continuing education course in implantology for dentists: a retrospective cross-sectional survey - Yunyi Xie; Junda Li; Qianmin Ou; Jinming Wang (BMC Medical Education)
Abstract Background Continuing education courses are vital for cultivating dental specialists. In traditional dental continuing education, training for implant surgery is typically delivered through various forms of demonstrations (such as videos, images) in courses, but this learning method lacks interactivity and detailed information on surgical procedures. However, live surgery can address these limitations. The purpose of this study was to investigate whether live surgery as a new teaching methodology was acceptable for dentists in continuing education of dental implantology. Materials and methods The study conducted a survey of dentists from various hospitals or clinics who voluntarily participated in the annual national-level implantology continuing education training courses held by our institution from 2019 to 2024. Starting from 2022, live surgery demonstration courses were introduced. This study evaluated the satisfaction with the courses before and after the application of live surgery, as well as skill assessment guidelines. The learning outcomes was assessed by the dentists’ perceptions of the continuing education courses through the survey participation. Results In this study, 125 participating dentists filled out the questionnaires completely after the class of dentist continuing education. Before the introduction of live surgery courses, the rounded scores of most questions surpassed 3.5. After the introduction of live surgery courses, all the rounded scores surpassed 4.5 suggesting that a total agreement on all items was achieved. Participants attending the live demonstration courses reported higher satisfaction and skill assessment scores compared to those in the traditional courses. Conclusion The live surgery teaching indicates high acceptance and satisfaction rates by dentists. We highly encourage more dental institutions to launch live surgery courses to achieve positive learning outcomes for dentists.